Modeling, control, and implementation of the soft switching dc-dc converter for battery charging/discharging applications - Barsana Banu, J; Balasingh Moses, M (International Journal of Engineering and Technology, 2017)
This paper presents a soft switching bidirectional buck-boost converter for battery charging and discharging systems. The proposed method comprises of Inductance Capacitance Diode combination of the bidirectional dc-dc converter with one more electric switch is presented to accomplish high efficiency, high conversion ratio and maximum output power compared to the other bidirectional converters. It works in both steps up and steps down conversions. The proposed converter has alleviated the switching stress problems in the conventional bidirectional dc-dc converter. It suppresses the switching losses by zero voltage and zeroes current turn ON and OFF all switches. The complete steady-state analysis of the proposed bi-directional converter has described with its operating modes. Design consideration of parameters also presented to realize the converter characteristics. The switching stress on the power semiconductor devices is given, and the comparisons between the proposed technique and other bidirectional converters are illustrated with some results. Finally, the experimental prototype of 20 kHz, 315 W output power converter developed, and its feasibility verified through computer simulation results.